IMPROVING THE ORGANIZATION AND MANAGEMENT OF COST ACCOUNTING IN BUDGET ORGANIZATIONS (IN THE EXAMPLE OF HIGHER EDUCATION) (Marketing Journal, 2025)
This article examines the processes of organizing and maintaining expenditure accounting in budgetary organizations, particularly in higher education institutions. It highlights the current accounting system, principles of expenditure classification, and existing challenges in the accounting process. Furthermore, the study proposes modern approaches to improving expenditure accounting, including digitalization, automation, and strengthening financial control. The research results aim to enhance the efficien cy of fund utilization and increase financial transparency in higher education institutions. 123
Keywords: budgetary organizations; expenditure accounting; higher education; accounting; expenditure classification; digitalization; automation; financial control; efficiency; transparency